Analysis of Quality Cost Optimization at PT. XYZ in Gresik Regency - Savitri, Bragi Anestasya; Handayani, Anita (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
Quality is one of the main keys for the company's products, quality is also one of the hopes and desires of consumers. Companies will always try to maintain product quality before they fall into the hands of consumers, for this reason companies need to pay attention to the quality of each product. The company incurs quality costs in the hope that the products sent to consumers will not have defects or damage, but the company must also take into account the total quality costs so that there is no over budget, an efficient calculation of quality costs is 2.5% of total sales. This study aims to determine whether PT. XYZ has issued quality costs according to predetermined standards. The analysis used is descriptive analysis with a qualitative approach with the method of presenting quality cost ratios to assess the efficiency of quality costs. Based on the results of the analysis of PT. XYZ, PT. XYZ can see that the quality control costs carried out by the company in 2018 & 2019 are good, namely around 1.02% in 2018 and 1.03% in 2019, but in 2020 the quality costs do not meet the predetermined standards, namely 4.40% while the standard efficient cost of quality to sales of only 2.5%. This states that quality cost control in 2020 has not been carried out efficiently.